Public Perception on the Risk of Diabetes Mellitus and the use of Mulberry Leaf Extract in Normalizing Blood Glucose Level - Nurul Syameera, Aduka; Seng, Yan Ni (INTI International University, 2019)
This study was carried out to collect the status of public awareness and perception about risk of diabetes mellitus and usage of the Mulberry leaf extract for hyperglycaemic condition. This study’s involvement of human participants was in accordance with INTI International University’s ethical standard and ethical committee approval. Informed consent was obtained from all respondents in this study. The descriptive-frequency study was conducted in a total of 209 respondents around Nilai, Cheras and Kuala Lumpur through convenience sampling. Data were collected through a valid and reliable questionnaire, consisting of two sections. In total, 55% of respondents were in normal Body Mass Index (BMI) (18.5 – 24.9). However, there were 21% of respondents were overweight (25 – 29.9), 17% were underweight (<18.5) and 7% were obesity (30 – 40). The result showed that there were about 81% of respondents were unaware about their own blood glucose level and only 19% of respondents were reported to have regular health check up to know the blood glucose level. Furthermore, the respondents had chosen the exercise, followed with balance diet and thirdly practising optimal healthy habit in achieving healthy life style. The least to be chose in achieving healthy life style was medication. Overall results in this study reported that the majority of respondents are not aware about function of Mulberry leaf in normalizing the blood glucose level. There were only 12% of respondents had reported to consume Mulberry leaf extract. And 6% of respondents had consume it before and claimed to feel no changes after consumption. The findings indicated that the community and public awareness towards risk of diabetes and potential value of Mulberry leaf consumption need to be improved especially among teenagers and young adults to cultivate good health promotion and natural product consumption for beneficial.